Pan-tissue mitochondrial phenotyping reveals lower OXPHOS expression and function across cancer types - Ilya N. Boykov; McLane M. Montgomery; James T. Hagen; Raphael T. Aruleba; Kelsey L. McLaughlin; Hannah S. Coalson; Margaret A. Nelson; Andrea S. Pereyra; Jessica M. Ellis; Tonya N. Zeczycki; Nasreen A. Vohra; Su-Fern Tan; et al. (Scientific Reports, 2023)
Abstract Targeting mitochondrial oxidative phosphorylation (OXPHOS) to treat cancer has been hampered due to serious side-effects potentially arising from the inability to discriminate between non-cancerous and cancerous mitochondria. Herein, comprehensive mitochondrial phenotyping was leveraged to define both the composition and function of OXPHOS across various murine cancers and compared to both matched normal tissues and other organs. When compared to both matched normal tissues, as well as high OXPHOS reliant organs like heart, intrinsic expression of the OXPHOS complexes, as well as OXPHOS flux were discovered to be consistently lower across distinct cancer types. Assuming intrinsic OXPHOS expression/function predicts OXPHOS reliance in vivo, these data suggest that pharmacologic blockade of mitochondrial OXPHOS likely compromises bioenergetic homeostasis in healthy oxidative organs prior to impacting tumor mitochondrial flux in a clinically meaningful way. Although these data caution against the use of indiscriminate mitochondrial inhibitors for cancer treatment, considerable heterogeneity was observed across cancer types with respect to both mitochondrial proteome composition and substrate-specific flux, highlighting the possibility for targeting discrete mitochondrial proteins or pathways unique to a given cancer type.